Forensic risk assessment: a metareview, novel meta-analysis, and empirical study developing a violence screening tool for schizophrenia - Singh, J; Jay P Singh (2011)
Mental health professionals are routinely called upon to assess the violence risk of their patients. An increasingly common method for conducting such assessments is the use of structured risk assessment tools. The aim of this thesis was to investigate the utility of such instruments: to identify and explore current uncertainties concerning their applicability and to design a novel measure that could be used as part of a stepped strategy to risk assessment. Though a number of risk assessment tools have been developed and there is a considerable literature concerning their psychometric properties, uncertainty remains regarding their effective use. In order to identify key contemporary uncertainties, a metareview of the forensic assessment literature was conducted. The metareview found that previous systematic reviews and meta-analyses of the risk assessment literature have come to conflicting conclusions on a number of issues, including the comparative predictive validity of risk assessment tools, the efficacy of actuarial tools versus clinical judgement, and the influence of demographic factors and study design characteristics on predictive accuracy. These uncertainties were then investigated in a comprehensive meta-analysis of nine commonly used risk measures. The meta-analysis concluded that there were significant differences between the predictive validity of the risk assessment tools, with instruments designed for more specific purposes performing better than those designed for more general use. Tools performed best when administered to samples demographically similar to their calibration sample. Actuarial instruments and structured clinical judgement were found to perform comparably. The final study presented in this thesis explored the feasibility of a stepped approach to risk assessment in which individuals at very low risk of future violence are screened out prior to resource-intensive clinically based assessment. High-quality national registers were used to construct a simple tool to identify patients with schizophrenia at very low risk of violent conviction after being discharged from hospital. The tool was found to produce high rates of sensitivity as well as high negative predictive values at 1, 2, and 5 years follow.up. In light of the findings of these three studies, risk assessment procedures and guidelines by mental health services and criminal justice systems may need review.